1996
DOI: 10.1056/nejm199601183340301
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1Mutations in a Population-Based Sample of Young Women with Breast Cancer

Abstract: Alterations in BRCA1 were identified in approximately 10 percent of this cohort of young women with breast cancer. The risk of harboring a mutation was not limited to women with family histories of breast or ovarian cancer. These results represent a minimal estimate of the frequency of BRCA1 mutations in this population. Comprehensive methods of identifying BRCA1 mutations and understanding their importance will be needed before testing of women in the general population can be undertaken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
121
4
3

Year Published

1996
1996
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(143 citation statements)
references
References 26 publications
15
121
4
3
Order By: Relevance
“…This figure is remarkably similar to the proportion of women with breast cancer under 40 years of age estimated by genetic epidemiological methods to be caused by mutations in the BRCAJ gene of 5.3% (Ford 1995) and found in practice by others (Langston et al, 1996;Struewing et al, 1996;Couch et al, 1997).…”
Section: Discussionsupporting
confidence: 82%
“…This figure is remarkably similar to the proportion of women with breast cancer under 40 years of age estimated by genetic epidemiological methods to be caused by mutations in the BRCAJ gene of 5.3% (Ford 1995) and found in practice by others (Langston et al, 1996;Struewing et al, 1996;Couch et al, 1997).…”
Section: Discussionsupporting
confidence: 82%
“…The contribution of such carriers to the overall incidence of BRCA1 mutations is as yet unknown. In two recent studies the incidence of mutations was found to be 13% in women with breast cancer diagnosed before the age of 30 (FitzGerald et al, 1996) and 10% in women diagnosed with breast cancer under the age of 35 (Langston et al, 1996a). Two out of six mutation carriers from the latter study did not report any family history of breast or ovarian cancer.…”
Section: Discussionmentioning
confidence: 86%
“…The observed high frequency of the 12 bp insertionduplication in intron-20 and its distribution in the studied groups is intriguing. In earlier reports this insertion was in each case associated with the serious medical history of malignant conditions and was not detected in numerous controls (Takahashi et al, 1995;Langston et al, 1996a;Langston et al, 1996b). In one of these studies the carrier was a woman with both breast and ovarian cancer who had ®ve maternal relatives with breast cancer (Takahashi et al, 1995).…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…One implication of this is that quite a sizeable fraction of breast cancers below the age of 35 years may involve constitutive or inherited mutant genes. As some will be new mutants in the germ line, not all young patients will have a prior family history of breast cancer (Langston et al, 1996).…”
Section: Introductionmentioning
confidence: 99%